The Theoretical Evaluation for the Possibility of the CoO(OH)-Assisted Electrochemical Detection in Water - Романів, Людмила Вікторівна (Applied Journal of Environmental Engineering Science, 2017)
The possibility of pyriproxyfen electrochemical detection in water (in neutral, or alkaline pH conditions), assisted by CoO(OH), has been studied. By means of mathematical model development and analysis, using the linear stability theory and bifurcation analysis, the analytical efficiency conditions have been detected. The oscillatory and monotonic instability conditions have also been detected.
Keywords: Intoxication prevention, Pyriproxyfen, Electrochemical detection, Cobalt (III) Oxyhydroxide, Mathematical modeling, Stable steady-state.